MOTIVATION OF PREGNANT WOMAN TO IMPLEMENT THE PREGNANCY GYMNASTIC - veryudha eka prameswari; Synta Novyana Selly (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Pregnancy gymnastics is not something new in Indonesia, but many pregnant women who are lack of knowledge or even do not know about pregnancy gymnastics. One of the impacts caused if the mother does not perform pregnancy gymnastic is a complaint that will be felt more than the mother who exercises pregnancy exercise. This research aimed to determine the motivation of pregnant women to implement pregnancy exercise in BPM Titi Ekawati STR, Keb Tampung Rejo Kecamatan Puri Mojokerto regency. The research design was descriptive. The population in this research was trimester II and III pregnant women in BPM Titi Ekawati STR, Keb Tampung Rejo Kecamatan Puri Mojokerto regency in 2016 which amounted to 16 people. The sampling technique used total sampling. The variable of research was the motivation of pregnant mother to carry out pregnancy exercise. Measuring tools using questionnaires. The result showed that respondents had high motivation as much as 1 respondent (6.2%), 13 respondents (81.2%) had moderate motivation, and 2 respondents (12,5%) had low motivation. Data analysis used is frequency distribution and percentage. Medium motivation is owned by pregnant women because mothers only do pregnancy exercises if there is something to be desired, namely the presence of blood tests during pregnancy exercise classes. Pregnant women should be more motivated to do pregnancy gymnastic because it has benefits for pregnancy and before childbirth. Mothers can do pregnancy gymnastic that is held every 1 month or done in each home. Keywords: motivation, pregnancy gymnastic